(untitled) (Agricultural Engineering, 2020)
The paper presents the results of research on the mass and the energy potential of malting barley straw of the “Klas” variety. The research was designated on a 100 ha plantation located in Pojezierze Iławsko-Sztumskie region. Using the Yara N-Sensor processor, precise application of mineral fertilizers according to determined fertilization demand allowed increasing the grain yield by 26% and the straw biomass yield by 74% compared to the control sample. The resulting increase in bio-mass obtained in the form of straw impacts its possible partial use for energy purposes without negative effects on the environment. The tested energy value of malting barley straw as a function of moisture content allowed a conclusion that between 10 and 25% of water content the energy value drops from 13.1 to 7.4 GJ∙t−1. For an average water content of 15%, this yields an energy potential unit of 23.76 GJ∙ha−1. Following observations of the combustion process, it was concluded that barley straw cannot be used as a source of biomass for the large-scale power production since its ash melts at below 800ºC.